Bahasa Inggris - Hernawati; Elita Maydasari; Riki Sahman (Postgraduate, University of Mataram, 2025)
The demand for garlic is increasing along with population growth The increase in garlic consumption over time if not balanced with an increase in domestic production will lead to increasing dependence on imports. The purpose of this paper is to analyze: Analyze production factors that influence productivity; Estimate the level of technical efficiency; and Analyze socio-economic factors that influence technical inefficiency in garlic farming. The sample was 40 samples. The sample was determined intentionally (purposive). Estimation of technical efficiency used Stochastic Frontier (SFA) with the Cobb-Douglas production function model. The results of the study indicate that factors that influence increasing garlic production are land area, urea fertilizer, ZA fertilizer, NPK fertilizer, and family labor. Input factors that have a significant influence as risk inducing factors are ZA fertilizer, insecticides, herbicides, and labor within and outside the family. Input factors that have a significant influence in reducing technical inefficiency are NPK fertilizer. There are no input factors that significantly increase technical inefficiency; Technical efficiency reaches an average of 0.87 which indicates that there is still a 13% opportunity for farmers to increase production to their frontier using existing technology; and Socio-Economic Factors that influence technical inefficiency are influenced by experience.